Upgrading SME’s Marketing Performance: Adaptive, Innovative Capability, and Isolating Mechanism - Gunarso Wiwoho; Sulis Riptiono (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
Business competition requires companies always to behave adaptively, but not all adaptations carried out by companies can improve performance. Because of that, this research aims to examine the role of adaptive capability, isolating mechanism product advantage, and product innovation capability on marketing performance in a research model. This research was conducted using a sample of 271 owners of Batik Tulis business in Barlingmascakeb, Central Java. Sampling was done using a purposive sampling technique, and the research method used was SEM-AMOS. The research results show that adaptive capability, isolating mechanism product advantage, and product innovation capability have proven to improve marketing performance in Batik Tulis SMEs. However, the relationship between adaptive capability cannot be proven to influence product innovation capability. Adaptive capability also plays a key role in improving marketing performance because it has the most significant influence compared to other variables used in this research.